Design ’70, czyli „chały nie było” - Kliś, Łukasz (Człowiek i Społeczeństwo, 2017)
Łukasz Kliś, Design ’70, czyli „chały nie było” [Design’70 or „trash was not there”], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 77-88, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. Opinions about Polish design in the seventies are divided. But many examples prove that it was quite a good time for Polish design: like Polish road letters system – designed by Marek Sigmund during one month. It was an extremely big challenge – a question of a short time and easy-to-use tools as possible to fix the visual communication problem on every Polish road by unprofessional staff. Polish road letters still work! Or Polish gliders, which were among the best in the world; not only being able to win most important competitions, but also of a beautiful form. In People’s Poland there were total designers too, like Tadeusz Ciałowicz in Wroclaw. He designed furniture, neon lighting, posters, interiors of shops, trademarks – all in the exquisite quality. Design and visual communication education was developed according ideas taken from Western Europe schools (such was the case of Krzysztof Lenk’s design atelier in Fine Art Academy in Łódź).